Aspek Semantik Teks-Teks Dongeng Skriptorium Pakualaman: Studi Naskah Sĕstra Agĕng Adidarma (Pi.35) - Rahmat, Rahmat; Sangidu, Sangidu; Saktimulya, Sri Ratna (Kamaya: Jurnal Ilmu Agama, 2025)
The Sĕstra Agĕng Adidarma manuscript (abbreviated as SAA) with the code Pi.35 is a manuscript written in the mid-19th century in Pakualaman, Yogyakarta. It contains several texts, including various folktales. The aim of this study is to identify the number of folktale texts in the SAA manuscript and to analyze them narratively to uncover their structural composition. The theory employed is philology, supported by the narrative structure approach developed by Tzvetan Todorov, particularly focusing on semantic aspects. The benefit of this research is to present the distinctive characteristics of folktale texts from Pakualaman. The results show that there are 26 folktale texts in the SAA manuscript. The semantic aspects of the texts indicate that formally, the texts are composed in the form of macapat verse poetry. The chosen opening tembang (verse forms) include: Pangkur (2 texts), Sinom (8 texts), Asmaradana (6 texts), Dhandhanggula (7 texts), Gambuh (3 texts). The folktales convey allegorical meanings through human and animal characters. Substantively, the folktales in the SAA manuscript reflect aspects of human life, including traits such as character, deceit, incitement, gratitude, carelessness, obedience to orders or prohibitions, leadership, loyalty, justice, and inheritance.